Development and Validation of a Stability-Indicating RP-HPLC Method for the Simultaneous Estimation of Atorvastatin and Ezetimibe in Bulk and Pharmaceutical Dosage Forms: Research Article (Journal of Pharma Insights and Research, 2026)
Simultaneous therapeutic management of hyperlipidemia and cardiovascular risk profiles frequently relies on combination of HMG-CoA reductase inhibitors and selective cholesterol absorption inhibitors. Analysis of such co-formulations requires robust, reliable, and stability-indicating methodologies. An isocratic reversed-phase high-performance liquid chromatography method was developed and validated for the concurrent quantitative determination of Atorvastatin and Ezetimibe in both active pharmaceutical ingredient forms and commercial tablet formulations. Chromatographic separation was achieved on a C18 stationary phase (250 mm  4.6 mm, 5 µm) utilizing a mobile phase consisting of methanol and 0.1% formic acid in a 60:40 v/v ratio. The system operated at a flow rate of 0.8 mL/min with a column temperature maintained at 25∘C, and detection was performed at an isosbestic wavelength of 239 nm. The retention times for Atorvastatin and Ezetimibe were established at approximately 3.3 and 6.1 minutes, respectively. The analytical method exhibited excellent linearity over a concentration range of 5-25 µg/mL for both analytes, with correlation coefficients exceeding 0.999. Accuracy was confirmed by standard addition recovery studies, yielding recoveries between 98.35% and 102.06%. Forced degradation studies under hydrolytic, oxidative, photolytic, and thermal stress conditions indicated that the method effectively resolves degradation products from the active drug peaks. Ezetimibe showed extreme susceptibility to alkaline hydrolysis, achieving complete degradation, whereas Atorvastatin displayed moderate stability across all stress environments. The validated method meets all the validation criteria, proving its utility for routine pharmaceutical quality control and stability assessment